Bahasa Remaja pada Usia Dewasa dalam Film Bebas - Royyi Muwaffa (LPPM STKIP PGRI Bandar Lampung, 2023)
Based on age groups, languages ​​can be divided into three groups, children's speech groups, youth speech groups, and adult speech groups. The speech of adolescents is more varied than that of children and adults. Teenage speech is synonymous with the use of slang languages. This is not only applied in daily conversation but also used in social media, advertisements, even films as in film of Bebas. In the film of Bebas, slang is not only used by teenagers but also used by adults. The theory used in this study is the theory of adolescent language. The language of adolescents cannot be classified in detail because its development is very broad and rapid, giving rise to new kinds of new languages. The method used is descriptive method with listening and note technique. Based on the results of the study, several slang languages ​​can be classified into four forms, namely greetings, verbs, adjectives, and nouns.